The effects of nanosilica fertilizer concentration and dose of rice hull ash on the characteristic of soybean leaves (Glycine max L. Merril). (March 2019) - Suciaty, T; Supriyadi,; Sakya, A T; Purnomo, D
Abstract: Utilization of nanosilica fertilizer and rice hull ash in soybean cultivation is an environmentally friendly cultivation that supports sustainable agriculture. The purpose of the research was to analyze the effects of nanosilica fertilizer and dose of rice hull ash on characteristics of soybean leaves. The study was arranged as factorial design with two factors. The first factor was nanosilica fertilizer, consisted of four levels (0, 1.25, 2.5- and 3.75-ml l −1 ). The second factor was dose of rice hull ash consisted of four levels (0, 1, 2 and 3-ton ha −1 ). Each treatment combination was repeated three times. Concentration of nanosilica individually affect the number of leaves at 29 and 43 days, leaf area and the leaf area index at 43 days. There was interaction between nanosilica fertilizer and rice hull ash on leaf thickness, stomata density, trichome density and silica content in leaves. Combinations of 1.25 ml l −1 nanosilica and 1-ton ha −1 rice hull ash gave the highest leaf thickness, combination of 1.25 ml l −1 nanosilica and 2-ton ha −1 rice hull ash gave the highest stomata density and silica content in leaves. Combination of 1, 25 ml l −1 nanosilica fertilizer and 3-ton ha −1 rice hull ash gave the highest trichome density.